The impact of the COVID-19 pandemic on routine HIV care and cervical cancer screening in North-Central Nigeria - Magdiel A. Habila; Mavis Obeng-Kusi; Maryam J. Ali; Francis A. Magaji; Iornum H. Shambe; Patrick H. Daru; Elizabeth T. Jacobs; Purnima Madhivanan; Atiene S. Sagay; Jonah Musa (BMC, 2023)
Abstract Introduction Cervical cancer is the fourth most diagnosed cancer among women globally, with much of the burden being carried by women in limited-resource settings often worsened by the high prevalence of HIV. Furthermore, the COVID-19 pandemic disrupted organized screening efforts and HIV management regimens worldwide, and the impact of these disruptions have not been examined in these settings. The purpose of this paper is to describe whether uptake of cervical cancer screening and HIV management changed before, during, and since the COVID-19 pandemic in North-Central Nigeria. Methods Longitudinal healthcare administration data for women who obtained care between January 2018 and December 2021 were abstracted from the AIDS Prevention Initiative Nigeria (APIN) clinic at Jos University Teaching Hospital. Patient demographics, pap smear outcomes, and HIV management indicators such as viral load and treatment regimen were abstracted and assessed using descriptive and regression analyses. All analyses were conducted comparing two years prior to the COVID-19 pandemic, the four quarters in 2020, and the year following COVID-19 restrictions. Results We included 2304 women in the study, most of whom were between 44 and 47 years of age, were married, and had completed secondary education. About 85% of women were treated with first line highly active retroviral therapy (HAART). Additionally, 84% of women screened using pap smear had normal results. The average age of women who sought care at APIN was significantly lower in Quarter 3, 2020 (p = 0.015) compared to the other periods examined in this study. Conversely, the average viral load for women who sought care during that period was significantly higher in adjusted models (p < 0.0001). Finally, we determined that the average viral load at each clinic visit was significantly associated with the period in which women sought care. Conclusions Overall, we found that COVID-19 pandemic mitigation efforts significantly influenced women's ability to obtain cervical cancer screening and routine HIV management at APIN clinic. This study buttresses the challenges in accessing routine and preventive care during the COVID-19 pandemic, especially in low-resource settings. Further research is needed to determine how these disruptions to care may influence long-term health in this and similar at-risk populations.